2022
DOI: 10.3389/feart.2022.886120
|View full text |Cite
|
Sign up to set email alerts
|

Glacial-Interglacial Variations in Organic Carbon Burial in the Northwest Pacific Ocean Over the Last 380 kyr and its Environmental Implications

Abstract: The carbon cycle on the Earth’s surface is linked to long-term variations in atmospheric CO2 as well as carbon sequestration in various pools. The burial of particulate organic carbon (OC) in marine sediments is also highly sensitive to the global climate over geological time scales, but with little known about OC burial and its regulations over glacial-interglacial cycles. Here, we present a long-term OC record over the past ∼380 kyr, from the Northwest Pacific Ocean, an ideal region for studying OC burial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The deeper trough is mainly affected by NPIW, SCSIW or North Pacific Deep Water (NPDW) (Dou et al, 2015;Zhao et al, 2021). In a recent reconstruction of OC burial in the Northwest Pacific (water depth: 2670 m), it was shown that vertical water exchange was hindered due to the barrier formed by the enhanced glacial NPIW, so a hypoxic reducing environment was formed in the bottom water, which promoted the burial of OC (Zhang et al, 2022). We assumed that the water depth and topography of the site were crucial considering that core Z1 was collected from the west slope of the OT and the water depth was only 940 m. This location has been greatly affected by terrigenous materials and NPIW, so ventilation and related mineralization play important roles in regulating organic OC burial.…”
Section: The Mechanism Of Oc Burial In the Ot At The Glacial-intergla...mentioning
confidence: 99%
See 1 more Smart Citation
“…The deeper trough is mainly affected by NPIW, SCSIW or North Pacific Deep Water (NPDW) (Dou et al, 2015;Zhao et al, 2021). In a recent reconstruction of OC burial in the Northwest Pacific (water depth: 2670 m), it was shown that vertical water exchange was hindered due to the barrier formed by the enhanced glacial NPIW, so a hypoxic reducing environment was formed in the bottom water, which promoted the burial of OC (Zhang et al, 2022). We assumed that the water depth and topography of the site were crucial considering that core Z1 was collected from the west slope of the OT and the water depth was only 940 m. This location has been greatly affected by terrigenous materials and NPIW, so ventilation and related mineralization play important roles in regulating organic OC burial.…”
Section: The Mechanism Of Oc Burial In the Ot At The Glacial-intergla...mentioning
confidence: 99%
“…Many large rivers flow into the ECS, which causes the trough to receive tremendous detrital matter from East Asia. Compared with the continental shelf, the deeper water and slower sedimentation rate of the OT are conducive to preserving longscale paleoenvironmental information, providing high-resolution sedimentary records for the reconstruction of tectonic evolution, hydrological environmental changes, and global climate change during the Quaternary (Shinjo et al, 1999;Jian et al, 2000;Kao et al, 2005;Kao et al, 2006;Chang et al, 2009;Ujiiéet al, 2016;Li et al, 2017;Zhao et al, 2021;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%